BREAST CANCER IN NORTHERN PAKISTAN - Mohammad, Gul; zeb, Aurang; Shah, S. Humayun (Journal of Ayub Medical College Abbottabad, 1989)
ABSTRACT One hundred and twenty patients were treated for carcinoma of the breast at the District Head Quarter Teaching Hospital, Abbottabad from 1984-1989. The age at diagnosis appears to be bimodal with an early peak between 36 years and 40 years and a later peak between 60 years and 66 years. As expected, these patients were of high parity (median 5) and 96% of them had breast fed for an average of 16 months, late presentation with advanced systemic disease accounts for the dismal prognosis. Eighty-four percent of the patients presented with late disease and only 16% with early disease. Of the 25 patients, followed upto death, the median survival was 12 weeks. For various logistic reasons, long-term follow up was not possible for the remaining patients. To improve the outcome of breast cancer in our community an active educational programme is needed to increase the public awareness of the significance of beast symptomatology. Key words: breast cancer, late presentation.